Factors associated with allergic rhinitis in colombian subpopulations aged 1 to 17 and 18 to 59 (2016)
Background: Several studies have shown variations in the prevalence of allergic rhinitis (AR) around the world, and different potential predisposing factors. More studies are needed on risk factors, specifically in developing countries. This study explored the association of several factors and AR among urban residents in six cities of Colombia. Methodology: A cross-sectional study and a nested case-control study were carried out between 2009 and 2010 involving two Colombian subpopulations: children/adolescents and adults. Cases were affirmative respondents to “In the past 12 months, have you (or your child) had a problem with sneezing or a running or blocked nose, when you (or your child) did not have a cold or the flu?” “Controls” were subjects who never had been diagnosed with asthma, AR or atopic eczema by a physician, and whom did not report any symptoms in the past twelve months. Weighted logistic regression was used to assess the association of different factors with case/control status. Results: Factors associated with AR in children/adolescents were family history of AR, acetaminophen consumption and high socioeconomic status. Among adults, family history of asthma, AR and atopic eczema, and cetaminophen consumption were associated with AR. Consumption of cereals among children/adolescents and eating eggs among adults showed protective associations. Conclusions: Our findings suggest the presence of previously unknown cultural, environmental and family factors associated with the presence of AR in Colombia. © 2016, AMC. All rights reserved.